Problems and Strategies of Introvert Students in Speaking English - Putri, Seva Zakiyyah; Syafryadin Syafryadin; Muhammad Fadhli (UNIB Press, 2024)
In this research, researchers aims to find out the problems and causes of introverted students and introverted students' strategies in speaking English. Researchers used descriptive quantitative methods. In the first questionnaire researchers used a random sampling technique, in which 104 students of SMAN 4 Bengkulu in the Science majors grades 10 and 11 became the sample. And for the second and third questionnaires researchers used a purposive sampling technique, in which 67 students were categorized as introverts. The results of the study showed that introverted students have many problems in speaking English. The problem that most introvert students face is pronunciation problems in speaking English, with a total average of 2.01; then followed by the problem of lack of vocabulary (2.02); and the problem of lack of confidence (2.07). Researchers also found several causes of introverted students' speaking problems, namely students accustomed to using their mother tongue when forced to speak English (2.02) as the dominant cause based on the total average result; feeling lost the topic when speaking English (2.11), and feeling stuck in thinking (2.16). Then the last result, there are three strategies used by introverted students to overcome speaking problems. Metacognitive as the dominant strategy used by introvert students in overcoming speaking problems, the strategy is paying attention (3.25), then followed by cognitive strategies regarding practice strategies (2.79) and the socio-affective strategy regarding cooperative strategies (2.71). The problems and causes that most introvert students face in speaking English are pronunciation problems and students are used to using their mother tongue when they feel pressured. Furthermore, introverted students used many strategies with moderate mean total.